Representation of Social Morals in the Anime Demon Slayer: Swordsmith Village Arc: Moral Value Analysis from the Perspective of the Prophet's Hadith - Qurrotu A’yun (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Despite its high popularity, popular visual media such as anime often face negative stigma as mere entertainment that has little educational value or is even considered to have a bad impact. In fact, through in-depth analysis, narrative content in anime has a hidden potential to present and reflect universal moral values that are relevant to religious teachings, including in the context of Islamic morality. This research is directed to systematically identify the positive moral values contained in anime narratives, in the hope of adding to the discussion of the potential of anime as a medium of ethical inspiration and refuting the stigma that visual fictional content is only oriented towards negative aspects. The type of research used is qualitative-descriptive with a library research approach that makes the Demon Slayer Arc Swordsmith Village anime as the object of study. The primary data sources in this study were obtained from scenes and dialogues in the Demon Slayer arc Swordsmith Village anime, while secondary data sources were books, articles and journals related to the research. Data analysis uses thematic content analysis techniques to identify, categorize, and interpret values found systematically that are relevant to the Prophet's hadith